2020
DOI: 10.1097/sla.0000000000004054
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Resection in Pancreatic Cancer Surgery

Abstract: Objective:To investigate the perioperative and oncologic long-term outcomes of patients with LAPC after surgical resection at a high-volume center for pancreatic surgery.Background:The role of surgery in LAPC with arterial involvement is controversial.Methods:We analyzed 385 consecutive patients undergoing PAR (n = 195) or PAD (n = 190) of the encased artery for LAPC between January 1, 2003 and April 30, 2019.Results:There were 183 total pancreatectomies, 113 partial pancreatoduodenectomies, 79 distal pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 31 publications
2
39
0
3
Order By: Relevance
“…The large majority of studies on LAPC involve a small and very well selected group of patients, therefore there is a presence of selection bias. In a recent and large series published by one of the most experienced groups in the treatment of LAPC, the overall mortality rate was 8.8%, with a significant decrease to 4.8% in recent years (25).…”
Section: Lapc Resection and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The large majority of studies on LAPC involve a small and very well selected group of patients, therefore there is a presence of selection bias. In a recent and large series published by one of the most experienced groups in the treatment of LAPC, the overall mortality rate was 8.8%, with a significant decrease to 4.8% in recent years (25).…”
Section: Lapc Resection and Outcomesmentioning
confidence: 99%
“…Several attempts have been made to stratify patient prognosis based on the overall characteristics of a tumor instead of purely on anatomic features (22)(23)(24). With the improvement of oncologic therapy, studies have shown that arterial resections in well-selected cases can achieve similar longterm overall survival in experienced centers (9,25,26). The shift in this concept is critical as several reports have indicated that surgical resection after NAT for LAPC, even for metastatic PC, can give a significant increase in survival rate and even a chance for cure (16,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study covering nearly 40 years of experience showed that any type of arterial resection was performed at a frequency of 6% (44/730 patients) and confirmed the safety and efficacy of these operations for patients with locally advanced pancreatic cancer, additionally suggesting preoperative therapy with artery resection as a useful concept for locally advanced pancreatic cancer [ 76 ]. An important aspect in selecting patients properly and gaining sufficient surgical experience to safely perform such procedure which has recently been shown in two large series that demonstrated the impact of the surgical learning curve in two single center collectives of 111 and 195 patients, respectively [ 77 , 78 ].…”
Section: Surgerymentioning
confidence: 99%
“…Arterial resection with pancreatectomy remains controversial both because of increased perioperative morbidity and mortality but also less clear oncologic benefit. Nevertheless, pancreatectomy with arterial resection continues to be performed at experienced centers with acceptable outcomes in order to extend the benefits of surgery to more patients (7).…”
Section: Editorialmentioning
confidence: 99%